The Importance of microRNAs in RAS Oncogenic Activation in Human Cancer - Roncarati, Roberta; Lupini, Laura; Shankaraiah, Ram C.; Negrini, Massimo (Frontiers in Oncology, 2019)
microRNAs (miRNAs) regulate gene expression by modulating the translation of protein coding RNAs. Their aberrant expression is involved in various human diseases, including cancer. Several miRNAs are involved in the regulation of RAS (HRAS, KRAS or NRAS) and RAS-associated pathways. Dysregulated miRNA expression can lead to RAS activation irrespective of oncogenic mutations. miRNA-dependent RAS activation has shed light on some noteworthy indications. Besides being a relevant pathogenic mechanism, it represents a mechanism of resistance to target therapies against tyrosine kinase receptors and suggests a potentially useful approach for the control of RAS oncogenic activation.